2011
DOI: 10.1016/j.jhealeco.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Healthy school meals and educational outcomes

Abstract: This paper provides field evidence on the effects of diet on educational outcomes, exploiting a campaign lead in the UK in 2004, which introduced drastic changes in the meals offered in the schools of one borough - Greenwich - shifting from low-budget processed meals towards healthier options. We evaluate the effect of the campaign on educational outcomes in primary schools using a difference in differences approach; comparing educational outcomes in primary schools (Key Stage 2 outcomes more specifically) bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(122 citation statements)
references
References 29 publications
4
111
1
Order By: Relevance
“…A second control group with some form of intervention exposure, not related to school, and a longer-term follow up would be necessary to determine a sustainable impact. The Greenwich study (Belot & James, 2009) found changes persisting after one year, supporting the interpretation of a real effect. While attempts were made to measure the impact the food and dining room intervention, this was limited due to a lack of relevant and valid assessment tools.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…A second control group with some form of intervention exposure, not related to school, and a longer-term follow up would be necessary to determine a sustainable impact. The Greenwich study (Belot & James, 2009) found changes persisting after one year, supporting the interpretation of a real effect. While attempts were made to measure the impact the food and dining room intervention, this was limited due to a lack of relevant and valid assessment tools.…”
mentioning
confidence: 63%
“…Neither explored the impact of better eating at lunchtime on classroom learning behaviour. A recent study (Belot & James, 2009) comparing the impact of a campaign to improve school lunches in the London Borough of Greenwich against seven similar 'control' boroughs (i.e. no campaign) showed better average academic achievement scores at age 11 in English and Science and reduced authorised absenteeism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research documents that observing the Ramadan fast, leads to reduced activity, less desire to study and lower and concentration ability among a majority of the subjects (Afifi, 1997). Also research on the link between nutrition and cognition strongly suggests that nutrient intake is important for the cognitive functioning of schoolchildren (Belot and James, 2009;Benton, 2008;Maluccio et al, 2006;Muthayya et al, 2007;Pollitt et al, 1998;Simeon and Grantham-McGregor, 1989;Taras, 2005;Waterhouse et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…An exception is Maluccio et al (2006), who find for Guatemala that a nutrition intervention during the first three years after birth improved educational outcomes. Belot and James (2009) consider school meals in the United Kingdom. In a difference-in-differences setting they find that the switch from low-budget to healthier primary school meal improves outcomes and reduces absence.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes improved in English and Science, and authorized absences -linked to illness and health -fell by 14% (20). However, the children that benefited least were those from the lowest socio economic groups -those most in need of support.…”
Section: Early Life Experiencesmentioning
confidence: 99%